Human cross-protective antibodies to occluded epitopes in influenza hemagglutinin antigen - ADACHI, Yu; TONOUCHI, Keisuke; TAKAHASHI, Yoshimasa (Uirusu, 2019)
Protective antibody provides the most effective defense against influenza virus, and the aim of vaccination is to induce such antibodies in our body. Recently, novel classes of antibodies with ability to provide cross-group protection against antigenically divergent viruses were identified from humans and mice. A striking feature of the cross-protective antibodies is to target occluded epitopes that are hidden from antibody access under native trimeric HA structure; therefore, conventional influenza vaccines can not elicit such classes of antibodies at sufficient amounts for conferring broad protection. Here, we review how viruses protect these epitopes from antibody surveillance, and how antibodies against such occluded epitopes contribute to protection against virus infection. Also, we introduce the strategies for novel vaccines that induce cross-protective antibody response against the occluded epitopes.